When to Start a Fight and When to Fight Back: Liability Disputes in the Workers’ Compensation System - Card, David; McCall, Brian P. (Journal of Labor Economics, 2009)
Contrary to the original intention of no‐fault workers’ compensation laws, employers deny liability for a substantial fraction of on‐the‐job injuries. We develop and estimate a simple structural model that explains the high rate of litigation as a consequence of asymmetric information. We estimate the model using data for a large sample of back injuries in Minnesota. Simulations under the counterfactual assumption that all denied workers pursue their claims suggest that the strategic incentive accounts for 30%–40% of observed liability disputes.